Perilaku Petani Padi Dalam Penggunaan Pestisida Di Desa Mandalahurip Kecamatan Jatiwaras Kabupaten Tasikmalaya - Suryani, Dyah; Pratamasari, Rossy; Suyitno, Suyitno; Maretalinia, Maretalinia (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Pesticides are chemical compounds, microorganisms, viruses and other substances used to protect plant parts. Farmers expect yields from agriculture to increase so farmers use pesticides to eliminate pests and weeds. However, the use of pesticides has a negative side effect that is reduced biological and can be eliminated that is not targeted. This research is discussion about relation in knowledge, attitudes, age, education level and work period with pesticide use behavior. This type of research is observational analytic research with cross-sectional approach. The subjects of this research were Mandalahurip Village farmers who examined 96 farmers. The research instrument is a questionnaire. Data analysis using fisher analysis. The results of the analysis show that there is a relationship between knowledge and pesticide use behavior (p-value=0.019), there is a relationship between attitude and pesticide use behavior (p-value=0,000), there is no relationship between age and pesticide use behavior (p-value=0.531), no there is a relationship between level of education with pesticide use behavior (p-value=0.353), there is a relationship between work period and pesticide use behavior (p-value=0.015). The conclusion of this study is there is a relationship between knowledge, attitudes and years of service with pesticide use behavior in rice farmers and there is no relationship between age and education level with the behavior of the use of pesticides in rice farmers in Mandalahurip Village, Jatiwaras District, Tasikmalaya Regency.